PrEP knowledge, acceptability, and implementation in Ghana: Perspectives of HIV service providers and MSM, trans women, and gender diverse individuals living with HIV. - Akua O Gyamerah; Ezra Kinzer; Gloria Aidoo-Frimpong; Guro Sorensen; Matilda D Mensah; Kelly D Taylor; Naa Ashiley Vanderpuye; Sheri A Lippman (Public Library of Science (PLoS), 2023)
Pre-exposure prophylaxis (PrEP) could help reduce HIV incidence among cis men, trans women, and gender diverse individuals assigned male at birth who have sex with men (MSM, trans women, and GDSM) in Ghana, a group that bears a high HIV burden. Our study examined PrEP knowledge and acceptability, and barriers and facilitators to its uptake and implementation through qualitative interviews with 32 MSM, trans women, and GDSM clients living with HIV, 14 service providers (SPs), and four key informants (KIs) in Accra, Ghana. We interviewed participants about their PrEP knowledge, whether MSM would take PrEP, and what factors would make it easy/difficult to uptake or implement PrEP. Interview transcripts were analyzed using thematic analysis. There was high acceptability of PrEP use and implementation among MSM, trans women, GDSM, and SPs/KIs in Ghana. MSM, trans women, and GDSM interest in, access to, and use of PrEP were shaped by intersectional HIV and anti-gay stigma; PrEP affordability, acceptability, and ease of use (e.g., consumption and side effects); sexual preferences (e.g., condomless sex vs. condom use), and HIV risk perception. Concerns raised about barriers and facilitators of PrEP use and implementation ranged from medical concerns (e.g., STIs; drug resistance); social behavioral concerns (e.g., stigma, risk compensation, adherence issues); and structural barriers (e.g., cost/affordability, govern commitment, monitoring systems, policy guidance). Targeted education on PrEP and proper use of it is needed to generate demand and dispel worries of side effects among MSM, trans women, and GDSM. Free, confidential, and easy access to PrEP must be supported by health systems strengthening, clear prescription guidelines, and anti-stigma training for providers.